International Marketing - Onkvisit, Sak (Routledge, 2012)
The book has been fully updated with topical case studies, examples of contemporary marketing campaigns, the most relevant discussion topics as well as the most up-to-date theories, references and research findings. It is this combination of theory and practice that makes this textbook truly unique, presenting a fully rounded view of the topic rather than an anecodotal or descriptive one alone.